Determinants of the Capital Structure of Nigerian Listed firms: A Dynamic Panel Model - Sani, Abdullahi; Norfian Alifiah, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Firms in developing countries face high transaction costs and information asymmetry due to the undeveloped capital market conditions. This situation makes it difficult for the firms operating in the region to make a timely adjustment to the optimal leverage to enhance their value. Thus, the firms have to incur costs in their attempt to converge to their target debt ratio. Given this, it is imperative to examine the capital structure determinants using the dynamic model from the perspective of a developing country such as Nigeria. Therefore, this study examines the determinants of the capital structure of the Nigerian non-financial listed firms. The sample size of this research comprised the 71 firms listed on the floor of the Nigerian Stock Exchange during the years 2012 to 2018. The data for the study was obtained from the annual reports and accounts of the sampled companies and analyzed using the Generalized Method of Moments (GMM) estimator. The results of the study suggest that the Nigerian listed firms make a dynamic adjustment to attain an optimal leverage ratio. Also, the research suggests that firm size, tangibility, liquidity, and return on assets explain the attainment of target leverage of the Nigerian-listed firms. The evidence that emerged from this research has a policy implication for managers and investors in making their informed decisions. Managers should strive to operate at the optimum debt-equity level by taking adjustment costs into account when setting their capital structure.